Participatory Design: Effective Strategy for Enhancing Environmental and Social Economy in Low Income housing - Enet, Mariana (Editorial Pontificia Universidad Javeriana, 2012)
Traditionally, public programs for low-income housing in Argentina are developed with low customer participation in the design. Programs are defined without considering user´s cultural, environmental and productive conditions. Both official and external assessments present mismatches between use and design. This situation generate low housing occupation and maintenance, poor technical and environmental quality, low housing durability, grow of the energetic costs for housing thermal installations and frequently the loss of productive activities because of inadequate housing localization.